Shocks and growth: adaptation, precaution and compensation. - Goderis, B; Collier, P; Hoeffler, A (2006)
In this paper we investigate how a wide array of types of shock arising from world prices, natural events, and political violence affect growth. Our results suggest that the impact from political shocks are far greater than from natural shocks. However, our preliminary cointegration results suggest that the cost from primary commodity exporting are very large. Potentially shocks can affect growth either due to their impact, or due to the volatility that repeated shocks generate. In our empirical investigation we find little evidence that volatility is a problem. We investigate the efficacy of economic structure and domestic as well as external policy responses to the various shocks. What can a government do to moderate the adverse effects of negative shocks and to make the most of favourable shocks? The answer appears to be that governments can do a lot, partly through policies that alter exposure, partly through policies that encourage adaptation and flexibility, and partly by precautionary policies. Countries at risk are better placed with lower levels of debt, smaller fiscal deficits, and larger reserves. In addition international assistance can help to mitigate the impact of shocks. Development assistance as well as remittances can cushion the adverse effect of shocks.